Character Development in Higher Education: Implementing the Rabbani Learning Model in the Psychology Program at Muhammadiyah University, East Kalimantan - Marhani, Marhani; Masruhim, Muh. Amir; Warman, Warman (Technium Social Sciences Journal, 2025)
This study examines the implementation of the Rabbani Learning Model in fostering character development among students at the Psychology Program of Universitas Muhammadiyah Kalimantan Timur. The primary goal is to enhance students’ spiritual and moral awareness, promote empathy and social responsibility, improve academic and professional quality, and cultivate critical and creative thinking skills. The research adopts a case study approach, utilizing ethnographic methods, in-depth interviews, and document analysis of curriculum, activity reports, and program evaluations. Data collection was conducted through participant observation, semi-structured interviews, content analysis, and literature studies. The findings indicate that the Rabbani Learning Model is guided by five core principles: 1) Tauhid (recognizing the oneness of Allah SWT), 2) Khalifah (developing social responsibility), 3) Ilm (seeking knowledge for good), 4) Amal (applying knowledge in daily life), and 5) Ihsan (cultivating spiritual awareness and empathy). The model emphasizes the integration of worship and academics, development of spiritual character, and strengthening of noble morals, with an overarching focus on the awareness of Allah in every activity. In conclusion, the study demonstrates that the Rabbani Learning Model contributes significantly to curriculum development at Universitas Muhammadiyah Kalimantan Timur and offers a valuable framework for character-building in higher education. This model can be adapted by other educational institutions to improve the character quality of the younger generation.